Introduction to Epidemiology and Control of Peste des Petits Ruminants (Eco-PPR) tools. 1 Toolbox―Overview - Wieland, Barbara; Dione, Michel M.; Okoth, Edward A.; Jones, B.; Kotchofa, Pacem; Ilboudo, Guy S.; Campbell, Zoë A.; Rutto, Erick (International Livestock Research Institute, 2020)
This is an overview of all the tools that will be used to collect data within the Eco-PPR project.